Neurologic Complications in Patients with Cancer - Holroyd, Kathryn B.; Rubin, Daniel B.; Vaitkevicius, Henrikas (Seminars in Neurology, 2021)
Neurologic symptoms are commonly seen in patients with cancer and can be among the most challenging to diagnose and manage. It is often difficult to determine if new neurologic symptoms are secondary to direct effects of a malignant lesion, systemic complications of disease, paraneoplastic disorders, or side effects of cancer treatment itself. However, early diagnosis and treatment of each of these conditions can improve patients' quality of life and long-term functional outcomes. In this review, we describe a systematic approach to the diagnosis of new neurologic symptoms in patients with known malignancy. We have categorized the neurologic complications of cancer through a mechanistic approach, with an emphasis on ascertaining underlying pathophysiology to guide treatment choice. This review focuses on the acute neurologic complications of cancer that require hospital admission.
Keywords: metastases; paraneoplastic; CAR-T; immunotherapy; neurologic complications